Prompt gamma energy integration: a new method for online-range verification in proton therapy with pulsed-beams - Everaere, Pierre; Dauvergne, Denis; Gallin-Martel, Marie-Laure; Hérault, Joël; Koudia, Ayoub; Koumeir, Charbel; Létang, Jean Michel; Testa, Étienne (Frontiers in Physics, 2024)
We propose a method for prompt-gamma verification of proton range during particle therapy. This method, called Prompt-Gamma Energy Integration (PGEI), is based on the measurement of the total energy deposited in a set of detectors located around a patient. It is particularly suited in the case of high-instantaneous beam intensities, like for pulsed beams extracted from a synchro-cyclotron. GATE simulations show that millimetric range shifts can be measured at a beam-spot scale. The sensitivity is slightly degraded as compared to the Prompt-Gamma Peak Integration Method, for which Time-of-Flight can be employed to reduce the background in single-photon detection conditions at cyclotron accelerators. Experimentally, lead tungstate scintillators have shown to cope with the high instantaneous gamma count rates for PGEI at synchro-cyclotrons.